A combined wear-fatigue design methodology for fretting in the pressure armour layer of flexible marine risers - O'Halloran, S.M.; Shipway, P.H.; Connaire, A.D.; Leen, Sean B.; Harte, A.M. (Elsevier, 2017)
This paper presents a combined experimental and computational methodology for fretting wear-fatigue prediction of pressure armour wire in flexible marine risers. Fretting wear, friction and fatigue parameters of pressure armour material have been characterised experimentally. A combined fretting wear-fatigue finite element model has been developed using an adaptive meshing technique and the effect of bending-induced tangential slip has been characterised. It has been shown that a surface damage parameter combined with a multiaxial fatigue parameter can accurately predict the beneficial effect of fretting wear on fatigue predictions. This provides a computationally efficient design tool for fretting in the pressure armour layer of flexible marine risers.